Inhibitory Mechanisms Of Maillard Reaction Products - Laksmi Laksmi; H. M. Mochtar (Indonesian Chemistry Letter, 2002)
To determinine the inhibitory mechanism of antibacterial Maillard reaction products (PRM), heated mixtures containing GL (glukosa-tisin) and TU (molasses-urea) were were studied fcx their effect on uptake oxygen and iron solubility. It was found that the tested PRM had an inhibitory effect on the uptake of oxygen was observed. The PRM also had an effect on the solttbirity of iron in nutrient broth and in phosphate buffer. While the GL mixturereduced the solubility of iron it was increased by the TU mixture.